In Search of Public Values in Private Systems: A Response to the Montesquieu Lecture by Karen Yeung - Linnet Taylor (Tilburg Law Review, 2023)
This response to Yeung explores the political implications of the New Public Analytics, in relation to the theory of ‘orders of worth’. Firms engaging in NPA enter into both ethical and practical commitments with regard to their activities which impact on the public. This commentary identifies missing standards for what constitutes acceptable involvement by the private sector in facilitating, and setting the parameters for, interventions on the public. I argue that in large-scale interventions on the national or transnational scale, a conflation of public with commercial aims and values is occurring which requires a rethinking of the notion of procurement, but also of regulation. The engagements occurring under the definition of NPA raise the question of rule of law in new ways. To whom should regulation apply and at what point does a commercial firm become defined as a public-sector actor? How are firms escaping this definition, and what kind of response to this escape from scrutiny and regulation is appropriate?